2015
DOI: 10.1007/s11368-015-1191-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal dynamics of organic carbon in physically fractioned sediments associated with dam construction in the middle Lancang-Mekong River

Abstract: Purpose Dam construction alters hydrological conditions, impacting the sedimentary environment in the reservoir and modifying the regional flow of carbon. This study examined the spatial and seasonal dynamics of organic carbon in sizefractioned sediments to identify the role of physical protection (e.g. burial, aggregation) for preserving carbon and the potential impact of a dam on the mineralization of sedimentary organic carbon in the dammed Lancang-Mekong River. Materials and methods Sediment samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Based on 3 yr of geochemical survey results, we found that 1) sediment MMHg concentration tends to be higher at high TOC sites; 2) organic carbon sources of sediment and benthic fish are distinctive between river and estuary regions, but MMHg concentrations of sediment, SPM, and food web organisms are not distinguishable between the two regions; 3) the BSCF of MMHg is mostly determined by the trophic level of benthic fish rather than the sediment characteristics; and 4) a relatively low risk of MMHg exposure, via consumption of delta fish, to the local residents is expected. The current levels of TOC in Mekong Delta sediment are relatively low (0.2–1.5%), but multiple dam constructions are reinforcing the organic carbon sedimentation rate with increasing fine fractions (i.e., silts and clays) of sediment, especially in rainy seasons (Zhao et al ). In addition to dam construction, expanded shrimp aquaculture associated with salinity intrusion in the low‐lying delta area is currently enhancing the labile TOC supply to the surface sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 3 yr of geochemical survey results, we found that 1) sediment MMHg concentration tends to be higher at high TOC sites; 2) organic carbon sources of sediment and benthic fish are distinctive between river and estuary regions, but MMHg concentrations of sediment, SPM, and food web organisms are not distinguishable between the two regions; 3) the BSCF of MMHg is mostly determined by the trophic level of benthic fish rather than the sediment characteristics; and 4) a relatively low risk of MMHg exposure, via consumption of delta fish, to the local residents is expected. The current levels of TOC in Mekong Delta sediment are relatively low (0.2–1.5%), but multiple dam constructions are reinforcing the organic carbon sedimentation rate with increasing fine fractions (i.e., silts and clays) of sediment, especially in rainy seasons (Zhao et al ). In addition to dam construction, expanded shrimp aquaculture associated with salinity intrusion in the low‐lying delta area is currently enhancing the labile TOC supply to the surface sediment.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the organic matter is regulating the mobility of those pollutants in sediment [6,7,8]. In addition, some researchers are calculating the fraction of TOC with total sulfur while some other researchers determine the relationship between TOC and total nitrogen for the purpose of evaluation of the type of sedimentary environment and elucidate the dynamic of organic matter in sediment [2,3,9]. Hence, TOC is one of the important chemical sediment quality measurements that has been widely used in environmental evaluation analysis [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Surficial sediment is acting as the sink of TOC and other chemical pollutants as it is able to accumulate all the substances that have settled down on the bottom of water column, including particulate organic carbon and sediment particles which is attached with organic carbon substance [3,5,9]. Thus, surficial sediment is capable of reflecting the latest deposited pollution history [2,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation